(untitled) (International Journal of Environmental Sciences, 2025)
Background: Functional capacity in haemodialysis patients is affected due to respiratory muscles impairment. Physical activity is an important predictor of mortality in chronic kidney disease patients. CKD patients undergoing haemodialysis & manifested inactivity compared to sedentary individuals without CKD. The study aimed to investigate the effect of motivational interviewing & breathing exercises on functional capacity & quality of life (QOL) in chronic kidney disease (CKD) patients. Materials & methodology: This randomized clinical trial was conducted in patients on haemodialysis. A total of 70 patients participants randomized into two groups (35 in each group). The Experimental group (Group A) received motivational interviewing along with breathing exercises & Control group (Group B) received motivational interviewing. Functional capacity was assessed by 6MWT, while QOL was measured with SF - 36 Questionnaire scale. The study was conducted at the dialysis unit of Yashwantrao Chavhan Rural Hospital, Latur, for six weeks. Data were analysed by paired test to determine the effect of motivational interviewing & breathing exercise on functional capacity & QOL in CKD patients. Results: Functional Capacity was assessed by using mean and SD of pre-test and post-test for the Experimental Group which were 168.88 (SD ±41.214) and 319.71 (SD ±50.38) & the Control Group, the mean were 162 (SD ±47.823) pre-test and 240.85 (SD ±43.949) post-test, For Quality of Life, the Experimental Group’s mean scores before and after the intervention were 24.42 (SD ±5.591) and 75.09 (SD ±5.741). The Control Group showed pre-test and post-test mean scores of 27.66 (SD ±9.026) and 54.44 (SD ±7.132), respectively & After Motivational Interviewing, the mean score for Functional Capacity was 78.85 (SD ±34.194), and the mean Quality of Life score was 26.77 (SD ±10.1299). Both the Experimental Group (p=0.002) and Control Group (p=0.001) demonstrated significant effects on Functional Capacity and Quality of Life. However, the Experimental Group exhibited a more substantial effect, as indicated by a p-value of less than 0.05. Conclusion: Motivational interviewing, along with Breathing exercises, in the daily routine of patients with chronic kidney disease undergoing haemodialysis is recommended. This combination can effectively reduce impairments in respiratory function and improve physical performance.